Experimental Investigation on the Effect of Specimen Size in Determining Fracture Parameters of Concrete - Atur P. N. Siregar; M. I. Rafiq; M. Mulheron (Institute of Research and Community Outreach - Petra Christian University, 2016)
This paper presents the experimental results in investigating the effect of specimen size (ratio of beam width to aggregate size) on the value of stress intensity factor (KIC) and fracture energy (GF) using three-point bend (TPB). A test method recommended by RILEM was chosen to measure the KIC and the GF as fracture parameters. Three different specimen sizes of concrete beam with water/binder ratio of 0.2 and 0.30 were engaged in the experiments. Both qualitative and quantitative analyses based on the normalized stress against deflection curve, and the KIC and the GF were employed. Statistical analysis was carried out based on coefficient of variation of the measured value of fracture parameters in order to investigate the variability of corresponding results. It was found that specimen size have a relatively insensitive influence on the value of KIC, however, have a significant effect on the value of GF.